PERTANGGUNGJAWABAN PIDANA MEDIS TERHADAP KESALAHAN DIAGNOSIS PASIEN MENURUT UU NO. 36 TAHUN 2009 - Agnes Elyana Marbun; Cornelia Vanesa Sipayung; Emia Pepayosa Pinem; Sonya Airini Batubara (The Juris, 2021)
The purpose of this research is to find out how the criminal responsibility process of doctors in carrying out the medical profession to provide health services in accordance with professional standards and laws and regulations in Indonesia. This research uses normative juridical methods that are obtained from literature and literature related to doctor's obligations and sanctions such as books, journals and so on. Based on the results of research and discussion, doctors are obliged to provide health services in accordance with the standards of the doctor's profession. If the professional duties performed by the doctor or medical do not meet the applicable professional standards, then it can be held accountable for cases of malpractice as stipulated in article 360 paragraphs (1) and (2) of the Criminal Code containing elements of negligence. Law No.29 of 2004 on medical practice and Law No.36 of 2009 on health is a guarantee of medical malpractice with legal certainty that.